2015
DOI: 10.1021/acs.iecr.5b01841
|View full text |Cite
|
Sign up to set email alerts
|

Liquid Organic Hydrogen Carriers: Thermophysical and Thermochemical Studies of Carbazole Partly and Fully Hydrogenated Derivatives

Abstract: Carbazole derivatives are promising liquid organic hydrogen carrier (LOHCs). They can take up and release hydrogen in catalytic hydrogenation/dehydrogenation reactions. The thermophysical properties (heat capacity, density, viscosity, surface tension, and refractive index) of carbazole and N-ethylcarbazole, as well as those of their hydrogenated derivatives, were measured. Furthermore, thermochemical properties (enthalpy of vaporization, sublimation, and fusion) were derived from experiments. Molar enthalpies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 46 publications
1
43
0
1
Order By: Relevance
“…Therefore, N-ethylcarbazole, with a gravimetric density of 5.8 wt.%, has been identified as the most prospective candidate for hydrogen storage (Scheme 1). Although there are many studies about the dehydrogenation reaction from calculations and experiments [20][21][22][23][24][25][26][27][28], the dehydrogenation reaction is still the key to limit its large-scale application, especially, the development of dehydrogenation catalysts with outstanding activity and stability is the hotspot of current research. A large number of dehydrogenation catalysts have been extensively investigated, including homogeneous catalysts and the heterogeneous catalysts [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, N-ethylcarbazole, with a gravimetric density of 5.8 wt.%, has been identified as the most prospective candidate for hydrogen storage (Scheme 1). Although there are many studies about the dehydrogenation reaction from calculations and experiments [20][21][22][23][24][25][26][27][28], the dehydrogenation reaction is still the key to limit its large-scale application, especially, the development of dehydrogenation catalysts with outstanding activity and stability is the hotspot of current research. A large number of dehydrogenation catalysts have been extensively investigated, including homogeneous catalysts and the heterogeneous catalysts [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Für das LOHC‐System NEC/PH‐NEC wurden folgende thermodynamische Werte für die Gleichgewichtsreaktion in der Flüssigphase verwendet 14, 15: true6 normalH2 + normalC14 normalH13 normalN normalC14 normalH25 normalN trueΔ HnormalR 0 =-53,2 normalkJnormal normalmolnormalH2 -1 trueΔ GnormalR 0 =-18,2 normalkJnormal normalmolnormalH2 -1 trueΔ SnormalR 0 =117 normalJnormal normalmolnormalH2 -1 normalK-1 …”
Section: Variantenunclassified
“…It was found that the introduction of a nitrogen atom to aromatic organic hydrides is effective for lowering of the dehydrogenation temperature [1]. This idea was realized in N-alkyl-carbazoles as the second generation of nitrogen-containing organic hydrides for hydrogen storage [2][3][4]. So far, however, no single material has been found that can meet numerous criteria expected for the inexpensive but effective hydrogen storage material that must consume and release H 2 with fast kinetics at moderate temperatures of 350-400 K. Thus, the search for new LOHC systems based on abundant and inexpensive organic compounds with a high capacity to store and release hydrogen and ideally use the same catalyst to charge and discharge hydrogen under relatively mild conditions, and compatible with existing infrastructure for transport and refuelling, is a major challenge [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, these methods generally fail for aromatic, branched, and strained cyclic molecules [9]. In a series of our recent studies, we successfully tested quantum-chemical composite methods of G* family to provide reliable gas phase thermochemical data for N-alkyl-carbazoles [2][3][4]. The hydrogenation/dehydrogenation reactions suitable for hydrogen storage, however, usually take place in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%